"Speak Up" Programs. Issue 12 (December 2016) - Unknown
Abstract : Employee engagement is a vital component to union avoidance. Employees' perception that they lack a voice can be exploited by union organizers to persuade them they need a union to gain management's attention to their concerns. "Speak up" programs are a way for management to demonstrate the company does want to hear employees' views and values their contributions.